'The most remarkable man': James Croll, Quaternary scientist. (4th April 2022) - Edwards, Kevin J.
ABSTRACT: The year 2021 marked the bicentenary of the birth of James Croll (1821–1890), the self‐educated son of a crofter‐stonemason, whose life was characterised by a dizzying range of occupations and homes, poor health and financial concerns, and yet he became a pioneer of orbital dynamics and ice age climate change with an impressive record of publication. Drawing upon archival information and recently published observations, this paper explores selected aspects of Croll's biography, his scientific connections and controversies, and that area of his life relevant to Quaternary science. He was a 19th century polymath whose multifaceted contributions have been a catalyst for subsequent systems‐based climate science on the grand scale, including the foundations for the seminal work of Milutin Milankovitch on the rhythms of Quaternary environmental change.